Persepsi Mahasiswa Batak ISI Yogyakarta terhadap Komunikasi Budaya dan Simbol Lapo pada Film “Ngeri-Ngeri Sedap” - Afisyah, Chasilda; Sukmawati , Ade Irma (Jurnal Mahasiswa Komunikasi Cantrik, 2023)
This research discusses the perceptions of Batak students at ISI Yogyakarta regarding the Lapo culture in the film "Ngeri-Ngeri Sedap". The purpose of this study was to determine the respondents' perceptions of the topics raised. The method used in this research is corelations quantitative , with a positivistic paradigm approach. The theory used in this research is percepions theory, using the data collection technique used is purposive sampling, with data collection through online surveys using Google Form. Consists of 300 Batak student respondents at ISI Yogyakarta. The results of this study show that the average perception rate is above 3 which means true and agree, while the correlation results from this study are strong but do not influence each other, with a number of 0.400, the validity in this study is with a result of 0.569, so this research can be said to be significant.